China's Role in Global Governance in The Post-COVID-19 Era - Zhang Yun (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2023)
China's role in global governance has attracted the attention of the international community since 2018, and academic discussions on China's role have been continuing. As the global transformation, scholars pay more attentions to how China's status as a great power more and more impact global governance system and the word order. This paper discusses China's status in global governance from the perspectives of China's regional, international, and global identity. The article believes that China's role in global governance is firstly regional, and China's status in the international community is between a regional power and a global power. China still lacks the ability and willingness on global governance. China’s positioning in global governance is based on the original post-World War II United Nations Charter and China’s influence on global governance is constructive and complementary. China’s BRI is an international public good provided to the international community, especially to the Eurasian states and it has great impact on regional governance and global governance and will benefit the world.